Human papillomavirus multiplex ligation-dependent probe amplification assay for the assessment of viral load, integration, and gain of telomerase-related genes in cervical malignancies - Walraven-Theelen, Wendy; Litjens, Rogier J. N. T. M.; Vinokurova, Svetlana; Haesevoets, Annick; Reijans, Martin; Simons, Guus; Smedts, Frank; Herrington, C. Simon; Ramaekers, Frans C. S.; Knebel Doeberitz, Magnus von; Speel, Ernst-Jan M.; Hopman, Anton H. N. (Human pathology, 2013)
We evaluated the reliability of a novel multiplex ligation-dependent probe amplification (MLPA) assay in detecting integration of human papillomavirus (HPV) based on the viral E2/E6 copy number ratio in formalin-fixed and paraffin-embedded cervical lesions. The MLPA results were compared with those of amplification of papillomavirus oncogene transcripts for RNA, detection of integrated papillomavirus sequences for DNA, and HPV fluorescence in situ hybridization (FISH). DNA was isolated from 41 formalin-fixed and paraffin-embedded HPV-positive cervical lesions (cervical intraepithelial neoplasia grade 3 lesions, squamous cell carcinomas, and adenocarcinomas) for MLPA analysis. From 13 matching frozen samples, DNA and RNA were isolated for the detection of integrated papillomavirus sequences and/or the amplification of papillomavirus oncogene transcripts, respectively. Integrated HPV16, HPV18, or both were identified. The MLPA assay detected viral integration in 12 of these 13 cases, and episomal copies also were detected in 7 cases. In 20 of the 24 cases with exclusive viral integration or episomal viral copies as detected by FISH, MLPA confirmed the physical status of the virus. In the cases classified as mixed by FISH, the presence of excess episomal copies complicated the recognition of viral integration by MLPA. Furthermore, the feasibility of detecting gain of the telomerase genes with the HPV MLPA assay was evaluated. The MLPA confirmed the FISH data in 12 of 13 cases in which the status of copy number gain for telomerase RNA component was known. In conclusion, the HPV MLPA assay can be performed on routinely processed cervical lesions for the detection of viral load and HPV integration.
Gesehen am 03.02.2022